Did support for economic and political reforms increase during the post‐communist transition, and if so, why?1. Issue 2 (26th February 2013) - Rovelli, Riccardo; Zaiceva, Anzelika
Abstract We study the dynamics of individual support for changes in the economic and political system, using a unique dataset for 12 transition economies over the period 1991–2004. We document that support for transition was initially lower in the CIS countries and that there has been a converging trend in the support for reforms between the CIS and the Baltic and Central and Eastern European countries. We suggest several explanations for the initial divergence and the post‐98 convergence in support for transition between these three groups of countries, and show that economic growth, declining income inequality and improving quality of governance have contributed to increase the support for transition. In addition, we find that increased support for the market economy and democracy in the CIS is accompanied by a larger increase in trust towards the political institutions. Our results also confirm the implications of Aghion et al. (2010)'s model of a negative correlation between trust and the demand for government regulation.